Ishchenko N. G. Evaluative component lexical meaning - Ishchenko N. G. (Philological Treatises, 2020)
The article considers one of the components of connotation – evaluation and evaluative meaning of a word. Evaluation component is an approval or disapproval concluded in the meaning of the word. Evaluative meaning is a concept of high abstraction the contents of which allows an individual to vary the referent relation of the language unit.